Neuropsychopharmacology of Psychosis: Relation of Brain Signals, Cognition and Chemistry - Andre Schmidt (Frontiers Research Topics, 2015)
Previous research over the past decades has identified diverse neurobiological underpinnings of psychosis. In particular, by combining a variety of different neuroimaging modalities, it has been shown that psychotic states and the actual transition phase from a clinical high-risk state to established psychosis is characterized by structural, functional and neurochemical changes across different brain regions. Further evidence revealed that maybe not only focal brain abnormalities are characteristic for psychosis but specifically also an abnormal functional integration among various brain areas. Some evidence also suggests that dysfunctional brain connectivity proceeds during the development of psychosis when subjects perform a cognitive task. Notably, altered brain connectivity during cognitive challenges was often found to be associated with psychopathological measures, suggesting a mechanistic relation between functional network integrity and the clinical expression of psychosis. Several works proposed that disordered brain connectivity in psychosis results from abnormal N-methyl- D -aspartate receptor (NMDAR)-dependent synaptic plasticity, which can be mediated by other neurotransmitter systems such as dopamine or serotonin. Specific chemically mediated changes in synaptic plasticity may contribute to abnormal functional integration among brain regions and in consequence to impaired learning performances and inferences. Model-based connectivity investigations on synaptic signalling demonstrated for example that manipulation of the NMDA or α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor system altered synaptic plasticity in healthy volunteers, which was predictive for subjects' cognitive performance and psychopathology. In patients with psychosis, the activity in the prefrontal cortex during the processing of prediction errors, a specific form of learning, which is conveyed via synaptic connections, was linked with individuals' formation of delusions. These results fit well with many works suggesting that psychotic symptoms or also drug-induced psychosis-like experiences can be explained by disturbances within a hierarchically organized neuronal network, leading to maladaptive integrations of new incoming evidence and thereby to false formations of prediction errors and false beliefs. In this research topic, we like to cover the most recent neurobiological correlates for early stage psychosis and in particular for the prediction of psychosis by using different neurophysiological measures (e.g. structural and functional MRI, EEG, DTI or PET). Studies exploring effective connectivity or complex brain networks such as small-world properties with techniques like dynamic causal modelling, structural equation modelling, or graph theory analysis are highly appreciated. Very welcome are studies proving a link between clinical features such as psychopathology and cognition, brain signals, and chemistry (also in regard of antipsychotic treatments or substance-induced psychotic states). Moreover, environmental factors that may influence psychosis onset or its' developmental processes will be brought together with a diversity of different research modalities. We also collect critical reviews, mini-reviews or theoretical reflections from leading international researcher and clinicians in this field. The purpose of our research topic is intended to provide a state-of-the-art cognitive perspective to consider developing psychosis, which might shed more lights into the pathophysiological and neurobiological mechanisms of psychosis.